Solvent-free aqueous polyurethane dispersions - Fernandes, Isabel P. (2011)
The industrial production of aqueous polyurethane dispersions (PUDs) is nowadays a well established technology. There are two main synthetic routes to produce PUDs: the acetone process (a former process developed by Bayer AG) and the pre-polymer process (developed as an alternative response to the patented acetone process). Comparatively to the acetone process, the pre-polymer process has one major advantage since it requires none or only small amounts of acetone. The pre-polymer process, at present, is being forced to readapt due to ongoing developments, partly motivated by process constraints, raw materials restrictions and the need to obtain a true solvent-free product. Allied to this fact it is worth mentioning the European REACH legislation, which is having a considerable influence on the PUD industry. Most of the industrially produced PUDs use dimethylol propionic acid (DMPA) as the internal emulsifier. DMPA is sparingly soluble in the reactive mixture and needs to be previously dissolved in an organic solvent, usually Nmethyl- 2-pyrrolidone (NMP). NMP is difficult to remove and will remain in the final product. There are some alternatives to achieve the NMP-free concept. Among them we can refer the direct NM P replacement by an equivalent solvent, the DMPA replacement by an equivalent hydrophilising diol but with better solubility in the reactive mixture and the preneutralization of DMPA prior to reaction with isocyanates.